2019
DOI: 10.1371/journal.pone.0220367
|View full text |Cite
|
Sign up to set email alerts
|

Native seed, soil and atmosphere respond to boreal forest topsoil (LFH) storage

Abstract: During mining topsoil is salvaged and stockpiled until ready for reclamation, stockpiling can have detrimental effects on seed viability and soil quality. Research has assessed effects of salvage and placement depth of forest topsoil on plant community establishment, with little work on effects of storage, particularly in the boreal forest. Our research assessed boreal forest topsoil storage methods to determine effects on soil chemical and physical properties, native seed viability and germination and rhizome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Stockpiling may have a direct impact on soil propagule vitality (Mackenzie et al 2019; Dhar et al 2019; Shaughnessy et al 2022), as most of our cover soils were stockpiled 3 to 6 months except Sites 2 and 4 where stockpiling times for PMM were not well documented. Mackenzie et al (2019) found stockpiling can lead to significant losses in viability within 8 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stockpiling may have a direct impact on soil propagule vitality (Mackenzie et al 2019; Dhar et al 2019; Shaughnessy et al 2022), as most of our cover soils were stockpiled 3 to 6 months except Sites 2 and 4 where stockpiling times for PMM were not well documented. Mackenzie et al (2019) found stockpiling can lead to significant losses in viability within 8 months.…”
Section: Discussionmentioning
confidence: 99%
“…Reclamation outcomes depend on multiple factors including biotic and abiotic conditions and time since reclamation (MacKenzie et al 2012; Chen et al 2017; Dhar et al 2018; Mackenzie et al 2019). Abiotic site conditions such as cover soil type can play significant roles in plant community development (Chen et al 2017; Mackenzie et al 2019). In contrast, biotic factors such as microbial activity help soil formation and nutrient cycling (MacKenzie et al 2012; Macdonald et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical and chemical properties of stockpiled soil change during topsoil stripping, stockpiling, and storage. Stockpiling can increase soil bulk density, decrease microbial activity, reduce nutrient cycling, increase volumetric water content, and decrease seed viability (Strohmayer 1999; MacKenzie 2013; Mackenzie & Naeth 2019). Anaerobic conditions increase with the increasing depth of piles over time and are more severe in fine‐textured soils (Abdul‐Kareem & McRae 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Stockpile seed bank communities can be evaluated in different ways. For example, there are studies that quantify the decline in seed viability over time by burying seeds (Mackenzie & Naeth 2019) and other studies that compare the seed bank present in stockpiles at different depths (Iverson & Wali 1982; Dickie et al 1988; Golos & Dixon 2014). However, few studies have looked at the seed bank present in multiple stockpiles at once and compared those communities to the aboveground plant communities and nearby undisturbed areas.…”
Section: Introductionmentioning
confidence: 99%